2011
DOI: 10.1603/en11018
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Influences the Handling Efficiency of an Aphid Parasitoid Through Body Size-Mediated Effects

Abstract: It is well known that increasing the ambient temperature increases the metabolic rate and consequently, the foraging rate of most insects. However, temperature experienced during the immature stages of insects affects their adult size (an inverse relationship). Because body size is generally correlated to foraging success, we hypothesized that temperature indirectly influences the foraging efficiency of adult insects through developmental effects. We first investigated the role of parasitoid: host body size r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…A high developmental temperature would thus affect the parasitism rate of parasitoids not only through changes in host instar acceptance, but also through changes in their ability to parasitize large aphids. Similarly, Wu et al (2011) showed with Aphidius colemani attacking the green peach aphid Myzus persicae that large parasitoids reared at a cold temperature have similar handling times for both small and large aphids, whereas small A. colemani reared at a high temperature take longer to parasitize large aphids than small aphids.…”
Section: Foraging Temperaturementioning
confidence: 82%
See 2 more Smart Citations
“…A high developmental temperature would thus affect the parasitism rate of parasitoids not only through changes in host instar acceptance, but also through changes in their ability to parasitize large aphids. Similarly, Wu et al (2011) showed with Aphidius colemani attacking the green peach aphid Myzus persicae that large parasitoids reared at a cold temperature have similar handling times for both small and large aphids, whereas small A. colemani reared at a high temperature take longer to parasitize large aphids than small aphids.…”
Section: Foraging Temperaturementioning
confidence: 82%
“…Similarly, Wu et al . () showed with Aphidius colemani attacking the green peach aphid Myzus persicae that large parasitoids reared at a cold temperature have similar handling times for both small and large aphids, whereas small A. colemani reared at a high temperature take longer to parasitize large aphids than small aphids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an illustration, elevated temperature significantly reduced adult parasitoid longevity by about 51% in our laboratory experiment. This could be attributed to an increase in metabolic rate [52], which is likely to mediate many of the biotic impacts of climate change globally [53]. Alternatively, higher temperatures or increased metabolic rates could simply influence the way parasitoids invest their energy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar intraspecific variability is common among microhymenoptera and can be stimulated by alternative host species with different nutritional quality (Nalepa & Grisell, 1993; Medal & Smith, 2015) gregariousness with variable brood sizes (Harvey et al, 1998), and climatic differences, such as temperature (Wu et al, 2011). Ceraphronoids are parasitoids on insect parasitoid and predator larvae (Haviland, 1920; Withycombe, 1924; Kamal, 1939) and have a broad host range (Gilkeson, McLean & Dessart, 1993; Sullivan & Völkl, 1999).…”
Section: Introductionmentioning
confidence: 97%